An Overview of the Impact of Statin Therapy on Cardiac Incident Risk - Świrk, Urszula; Paprocka, Aleksandra; Kalinowska, Karolina; Fijałek, Paulina; Karczmarz, Jan; Gutowska, Marika; Kosińska, Agnieszka; Belcarz, Wiktoria; Orzechowska, Joanna; Orzechowski, Michał (Quality in Sport, 2025)
Statin therapy is a cornerstone in preventing and managing cardiovascular diseases, particularly in reducing the risk of cardiac incidents. This review presents a comprehensive overview of the impact of statin therapy on cardiac incident risk, examining its efficacy in primary and secondary prevention, the underlying mechanisms of action, associated adverse effects, and considerations for patient adherence. Evidence from large-scale randomized controlled trials and meta-analyses consistently demonstrates that statins significantly reduce the incidence of major cardiovascular events by lowering low-density lipoprotein (LDL) cholesterol levels and exerting pleiotropic effects like improving endothelial function and stabilizing atherosclerotic plaques. Although generally well-tolerated, statins may cause side effects, including muscle-related symptoms and a modest increase in the risk of type 2 diabetes. Patient adherence remains a critical factor in maximizing the therapeutic benefits of statin therapy.